Rethinking Ideal Education from Prospective Teachers' Perspectives: Systemic Challenges and Educational Policy Implications in Indonesia - Adnan Syah Sitorus; Dwi Ratnasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Contemporary educational reform in Indonesia has largely emphasized policy design and teacher implementation, yet limited attention has been given to how prospective teachers conceptualize ideal education and interpret systemic challenges. Addressing this gap, this study explores how pre-service teachers articulate their vision of ideal education and critically assess current educational conditions. Employing a qualitative case study design, data were collected from 33 fifth-semester students in an Islamic Education program through open reflective essays and analyzed using inductive thematic analysis. The findings reveal five interrelated dimensions shaping prospective teachers' conceptualization of ideal education: (1) learner-centered and meaningful pedagogy, (2) critique of assessment-oriented culture, (3) recognition of structural educational inequality, (4) awareness of professional pressures on teachers, and (5) integration of character education with 21st-century competencies. These themes demonstrate that prospective teachers' perspectives extend beyond classroom technique and reflect an emerging structural and professional consciousness. The study proposes an Ideal Education Framework that integrates pedagogical commitment, structural awareness, and systemic support as interconnected dimensions of educational transformation. This study contributes to the discourse on Indonesian educational reform by repositioning prospective teachers as reflective epistemic actors whose perspectives bridge pedagogical ideals and policy realities. The findings offer policy-relevant insights for strengthening teacher education, promoting equitable resource distribution, and balancing accountability with professional autonomy in national education reform.